2017
DOI: 10.1016/j.ymthe.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Endogenous MicroRNA System Dysfunction as a New Pathophysiological Mechanism in Machado-Joseph Disease

Abstract: Machado-Joseph disease (MJD) is a genetic neurodegenerative disease caused by an expanded polyglutamine tract within the protein ataxin-3 (ATXN3). Despite current efforts, MJD's mechanism of pathogenesis remains unclear and no disease-modifying treatment is available. Therefore, in this study, we investigated (1) the role of the 3' UTR of ATXN3, a putative microRNA (miRNA) target, (2) whether miRNA biogenesis and machinery are dysfunctional in MJD, and (3) which specific miRNAs target ATXN3-3' UTR and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 66 publications
3
39
0
Order By: Relevance
“…More recently, miRNA biogenesis was described to be impaired in MJD/SCA3, as several genes regulating that process are down‐regulated in different disease models (Carmona et al . ). The study also reported that three microRNAs (miR‐9, miR‐181a, and miR‐494) that interact with the 3′ untranslated region (3′UTR) of ataxin‐3 mRNA show a dysregulated expression in brain samples from MJD/SCA3 patients (Carmona et al .…”
Section: Therapeutic Perspectivesmentioning
confidence: 97%
“…More recently, miRNA biogenesis was described to be impaired in MJD/SCA3, as several genes regulating that process are down‐regulated in different disease models (Carmona et al . ). The study also reported that three microRNAs (miR‐9, miR‐181a, and miR‐494) that interact with the 3′ untranslated region (3′UTR) of ataxin‐3 mRNA show a dysregulated expression in brain samples from MJD/SCA3 patients (Carmona et al .…”
Section: Therapeutic Perspectivesmentioning
confidence: 97%
“…In a SCA3 animal model and human neurons, 3 miRNAs were identified that interact with the ATXN3 3′ UTR and whose expression is dysregulated. Injecting lentiviral vectors encoding for these miRNAs in the striatum of 5-week-old SCA3 mice resulted in reduction of ataxin-3 levels and nuclear aggregates and improvement of neuronal dysfunction [ 193 ]. Similar results have been obtained with adeno-associated virus (AAV)-mediated delivery of miR-3191-5p in SCA6 mice.…”
Section: Gene Therapiesmentioning
confidence: 99%
“…This phenomenon is further magnified because miR-9/9* transcription depends on REST. Aberrant expression of miR-9 has also been observed in the cerebella of mouse model of SCA3 [137] and SCA1 [140], being downregulated in SCA3 and upregulated in SCA1. The miR-9 dysregulation in SCA3 is proposed to be related with an impairment in miRNA biogenesis.…”
Section: Brain-enriched Mirnas Dysregulation In Polyq Disordersmentioning
confidence: 96%
“…Interestingly, ataxin-2, the protein involved in SCA2 disease, might be required for miRNA function, as lack of ataxin-2 impairs the repressive activity of several miRNAs [136]. In SCA3, miR-181a and miR-494, which interact with the ATXN3-3 -UTR, are found dysregulated in human MJD neurons as well as other MJD cell and animal models, and overexpression of these miRNAs alleviated MJD neuropathology in vivo [137]. In SCA17, downregulation of miR-29a and miR-29b is observed in a cellular model of SCA17, which was inversely correlated with BACE1 expression [138].…”
Section: Brain-enriched Mirnas Dysregulation In Polyq Disordersmentioning
confidence: 99%